KONSERVASI LAHAN TIDUR MENJADI DEMFARM KEBUN AGROMEDIKA HAMBARO (“KAMARO”) - Gunarto, Anton (BPPT)
Hambaro Agriculture Medical Farm (Kamaro) is sleeping land which is used for demonstration farming (demfarm) for agriculture medical plants. The aims of this research are (1) to plan, prepared and build demfarm for medical plants especially ginger, turmeric and temulawak, agriculture infrastructure, and another supporting building, (2) implemented land conservation technology with terrace-bench, cultivation and post harvest technology, and (3) introduce the technology to farmers’ around the farm. Form 2004 t0 2008 demfarm ginger production increased from 2.67 ton/ha to 3.50 ton/ha, turmeric production increased from 7.9 ton/ha to 16 ton/ha and temulawak production increased from 17.5 ton/ha to 25 ton/ha.Keywords : Land conservation, medical plants, Hambaro